Pengaruh Firm Size, Sales Growth dan Struktur Modal terhadap Kinerja Keuangan Perusahaan Manufaktur Sub Sektor Food and Beverage yang Terdaftar di BEI Periode 2020-2023 - Kusumaningrum, Rahayu; Armin, Rini; Verlandes, Yuliasnita (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Financial performance is an effort made by companies to measure their success in generating profits. This study aims to examine the impact of firm size, sales growth, and capital structure on the financial performance of manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) for the period 2020-2023. The sample was determined using purposive sampling, with a population of 99 companies. The data used is quantitative, sourced from financial statements published on the official IDX website. The analytical technique employed is multiple linear regression analysis. The results indicate that firm size does not affect financial performance; sales growth has a significant impact on financial performance; and capital structure has a significant impact on financial performance.